PENGARUH PELATIHAN, KOMPENSASI, DAN DISIPLIN KERJA TERHADAP MOTIVASI KERJA KARYAWAN (Studi Pada Koperasi Berkah Syariah Al-Fida Kota Bengkulu) - Vemy Vionika; Eti Arini (UM. Bengkulu, 2023)
Human Resources have a big role in determining the progress or development of the organization. The higher the quality of the human resources owned by the organization, the better the work motivation generated by HR at work. This study aims: To determine the effect of training, compensation, and work discipline on employees' work motivation Bengkulu) both partially and simultaneously. This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all 31 employees of the Al-Fida Syariah Berkah Cooperative, Bengkulu City. Based on the results of research on the Effect of Training, Compensation, and Work Discipline on Employee Work Motivation (Study on the Al-Fida Berkah Syariah Cooperative, Bengkulu City, the following conclusions can be drawn: 1). The training has a positive effect on the work motivation of the employees of the Alfida Syariah Berkah Cooperative. 2). Compensation has a positive effect on the work motivation of the employees of the Alfida Syariah Berkah Cooperative. 3). Work discipline has a positive effect on the work motivation of employees of the Alfida Syariah Berkah Cooperative. 4). Training, compensation and work discipline together show the effect on employee work motivation at the Alfida Berkah Syariah Cooperative. Keywords: Training, Compensation, Work Discipline and Work Motivation.